A Financial Playbook for Making Investment Decisions - Musa, Muhammad Ichwan; Aslam, Annisa Paramaswary; Aswar, Nurul Fadilah; Syahrul, Khaidir; Parawansa, Jalaluddin Mannagalli (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2024)
This study examines the influence of gender, age, education, living area and marital status as socio-demographic indicators and Â financial literacy toward investment decisions. The research was conducted in South Sulawesi, Indonesia with 167 respondents. The sample used was purposive sampling, with the specific criteria for the level of Indonesian wealth. Quantitative methods and a problem-solving approach were used. We found that gender has a negative and significant effect, education, living area, and marital status positively and significantly affect investment decisions. Women tend to prefer low-risk investments compared to men largely attributed to lower levels of financial literacy among women. In terms of education, investors with higher levels of education are more likely to make more informed investment decisions as they demonstrate improved risk management skills and a higher level of financial literacy. The living area also influences their investment decisions, with urban investors having easier access to information and knowledge about investments. Marital status also affects investment decisions, as married investors often prioritize the responsibility of their investments. However, age have a negative and not significant on investment decisions. This can be explained by the higher number of younger people becoming involved in investment decisions.